2017
DOI: 10.3847/1538-4357/aa6f17
|View full text |Cite
|
Sign up to set email alerts
|

Timing the Evolution of the Galactic Disk with NGC 6791: An Open Cluster with Peculiar High-α Chemistry as Seen by APOGEE

Abstract: We utilize elemental-abundance information for Galactic red giant stars in five open clusters (NGC 7789, NGC 6819, M67, NGC 188, and NGC 6791) from the Apache Point Observatory Galactic Evolution Experiment (APOGEE) DR13 dataset to age-date the chemical evolution of the high-and low-α element sequences of the Milky Way. Key to this time-stamping is the cluster NGC 6791, whose stellar members have mean abundances that place it in the high-α, high-[Fe/H] region of the [α/Fe]-[Fe/H] plane. Based on the cluster'… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
2
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 98 publications
(115 reference statements)
2
25
2
2
Order By: Relevance
“…We note that NGC 6791 is very metal rich, fairly old, and relatively far from the Galactic plane. Previous work using APOGEE data has suggested it likely migrated to its current location (Linden et al 2017). Since it is likely not representative of the region of the Galaxy in which it currently resides, we exclude it from further analysis.…”
Section: Ngc 6791 and The Metallicity Gradientmentioning
confidence: 98%
“…We note that NGC 6791 is very metal rich, fairly old, and relatively far from the Galactic plane. Previous work using APOGEE data has suggested it likely migrated to its current location (Linden et al 2017). Since it is likely not representative of the region of the Galaxy in which it currently resides, we exclude it from further analysis.…”
Section: Ngc 6791 and The Metallicity Gradientmentioning
confidence: 98%
“…On the contrary, NGC 6791 is an intriguing, old, very metal-rich, and massive system located almost 1 kpc above the Galactic plane. It has been suggested that NGC 6791 has likely migrated to its current location from its birth position (Linden et al 2017) or even has an extragalactic origin (Carraro et al 2006), although both claims are disputed. If we exclude these two clusters from the analysis, the [Fe/H] gradient flattens to −0.047 ± 0.004 dex kpc −1 .…”
Section: Galactic Trendsmentioning
confidence: 99%
“…Only a few of the clusters targeted by APOGEE have tens of observed stars (e.g., NGC 2420, NGC 6791, the Pleiades, or M 67; see, e.g. Cunha et al 2015;Linden et al 2017;Souto et al 2016Souto et al , 2018. About 20 clusters include 5-30 stars each, and those are the ones we focus on in this paper.…”
Section: Datamentioning
confidence: 99%